FAKTOR-FAKTOR YANG MEMENGARUHI AUDITOR SWITCHING SECARA VOLUNTARY - Nur Aini; Muhammad Aufa (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2023)
The aim of this study is to examine factors that affect auditor switching voluntarily. Variables that consider to have effect on auditor switching are audit tenure, change of management, size of public accountant firms, and financial distress. This study used 78 observation of annual report from palm oil companies that listed in Indonesia Stock Exchange period 2018-2021. The examination was used logistic regression to analyze and SPSS 25 as programmer. Result of the study stated that simultaneous audit tenure, change of management, size of public accountant firms, and financial distress significantly affect auditor switching voluntarily. Partially, change of management is the only variable that significantly affect auditor switching voluntarily. This study can be used by companies to consider voluntary rotation of auditor and auditor to improve performance in providing audit services. The limitation of this study are the use of the independent variables and the sample that used are not common sample so there was no concrete comparison.